An efficiency measurement of e-government performance for network readiness: Non-parametric frontier approach - Hyundong Nam; Taewoo Nam; Minjeong Oh; Sungyong Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Information and Communications Technology (ICT) network readiness competency improves service quality and provides efficient service in implementing successful e-governments. By confirming ICT network readiness of e-governments, it must be redesigned using limited resources effectively to achieve realistic goals. When ICT investment and economic performance are featured, e-government's network readiness competency improves potential demand, supply, and service maturity. It reflects information technology (IT) development competency on performance effectively. In this study, we propose the Data Envelope Analysis (DEA) method to present a method of improving ICT network readiness between countries. We derived the ICT network's readiness competency level and strategic plan by comparing each country for efficient ICT operation of e-governments. If we make rankings in a non-traditional and efficient manner, it will become a successful strategy for ICT in the future. This effort provides guidance for each government and a solution for the growth delay problem, which is required for advancement in ICT investment and productivity. It also guides each government to overcome marginal products.
Keywords: 650; e-government; efficiency strategy; ICT competitiveness; informatization; network readiness; user-centric ICT innovation